Research Trends on Ethnoscience-Based Learning Models with an Ethnopedagogical Approach to Train Students' Science Literacy and Learning Independence (2015-2024): A Systematic Review - Ariana, Lisa (Balai Publikasi Indonesia, 2025)
This study aims to describe the research trend of ethnoscience-based learning models with an ethnopedagogy approach as an effort to train students' scientific literacy and learning independence. With the background of technological developments that demand quality human resources, as well as the challenge of low scientific literacy in Indonesia, the ethnopedagogy approach is considered relevant to instill knowledge based on local wisdom. Through a bibliometric analysis of 500 articles in the period 2015 to 2024, this study shows fluctuations in academic interest related to ethnopedagogy learning models. The data shows a significant increase in 2018, followed by a decline due to the COVID-19 pandemic, before increasing again in the following years. The visualization of the keyword network highlights the main focus of research such as science process skills, the impact of the pandemic, and other innovative learning approaches. These results are expected to encourage further research in the development of scientific literacy based on local culture